More unsaturated, cooking-type hydrocarbon-like organic aerosol particle emissions from renewable diesel compared to ultra low sulfur diesel in at-sea operations of a research vessel. Issue 2 (1st February 2017) - Price, Derek J.; Chen, Chia-Li; Russell, Lynn M.; Lamjiri, Maryam A.; Betha, Raghu; Sanchez, Kevin; Liu, Jun; Lee, Alex K. Y.; Cocker, David R.
ABSTRACT: The aerosol particle emissions from R/V Robert Gordon Sproul were measured during two 5-day research cruises (29 September–3 October 2014; 4–7 and 26–28 September 2015) at four engine speeds (1600 rpm, 1300 rpm, 1000 rpm, and 700 rpm) to characterize the emissions under different engine conditions for ultra low sulfur diesel (ULSD) and hydrogenation derived renewable diesel (HDRD) fuels. Organic aerosol composition and mass distribution were measured on the aft deck of the vessel directly behind the exhaust stack to intercept the ship plume. The ship emissions for both fuels were composed of alkane-like compounds (H/C = 1.94 ± 0.003, O/C = 0.04 ± 0.001, C n H2 n ) with mass spectral fragmentation patterns consistent with hydrocarbon-like organic aerosol (HOA). Single-particle mass spectra from emissions for both fuels showed two distinct HOA compositions, with one HOA type containing more saturated alkane fragments (C n H2 n +1 ) and the other HOA type containing more monounsaturated fragments (C n H2 n −1 ). The particles dominated by the C n H2 n −1 fragment series are similar to mass spectra previously associated with cooking emissions. More cooking-type organic particles were observed in the ship emissions for HDRD than for ULSD (45% and 38%, respectively). Changes in the plume aerosol composition due to photochemical aging in the atmosphere were also characterized. The higher fraction of alkene or aromatic (C n H2 n − m, m ≥ 3) fragments in aged compared to fresh plume emissions suggest that some of the semivolatile alkane-like components partition back to the vapor phase as dilution increases, while alkene or aromatic hydrocarbons contribute more mass to the particle phase due to continuing photochemical oxidation and subsequent condensation from the vapor phase. Copyright © 2017 American Association for Aerosol Research